Virus and chlorine adsorption onto guanidine modified cellulose nanofibers using covalent and hydrogen bonding. (December 2020) - Mi, Xue; Albukhari, Soha M.; Heldt, Caryn L.; Heiden, Patricia A.
Abstract: Unsafe drinking water leads to millions of human deaths each year, while contaminated wastewater discharges are a significant threat to aquatic life. To relieve the burden of unsafe water, we are in search of an inexpensive material that can adsorb pathogenic viruses from drinking water and adsorb toxic residual chlorine from wastewater. To impart virus and chlorine removal abilities to cellulosic materials, we modified the primary hydroxyl group with a positively charged guanidine group, to yield guanidine modified cellulose derivatives. Microcrystalline cellulose (MC) bearing covalently bonded guanidine hydrochloride (MC-GC ) and hydrogen-bonded guanidine hydrochloride (MC-GH ) were synthesized, and electrospun into nanofibers after blending with the non-ionogenic polyvinyl alcohol (PVA), to produce large pore sized, high surface area membranes. The MC-GC /PVA and MC-GH /PVA nanofibers were stabilized against water dissolution by crosslinking with glutaraldehyde vapor. The water-stable MC-GC /PVA mats were able to remove more than 4 logs of non-enveloped porcine parvovirus (PPV) and enveloped Sindbis virus and reached 58% of chlorine removal. The MC-GC /PVA nanofibers demonstrated better performance for pathogen removal and dechlorination than MC-GH /PVA nanofibers. This first study of MC-GC /PVA electrospun mats for virus removal shows they are highly effective and merit additional research for virus removal. Graphical abstract: (Virus and chemical structure images were created in BioRender.). Image 1 Highlights: Synthetic routes to covalent and H-bonded guanidine on cellulose are given. Guanidine functionalized cellulose derivatives were electrospun into nanofibers. Glutaraldehyde crosslinking imparted water stability to the electrospun fibers. Over 4 log removal value was achieved for an enveloped and non-enveloped virus. Approximately 60% of chlorine removal was achieved.